Acknowledgement - Center of Excellence of Healthcare and Pharmacy Specialists informs, (Slauga. Mokslas ir praktika, 2020)
Padėka dėstytojams, programų vadovams, asmens sveikatos priežiūros įstaigų vadovams.
Keywords: acknowledgement; teachers; leaders of healthcare institutions; COVID-19 pandemic